Team performance indicators as predictors of final log position and team success in Aviva Premiership, Guinness Pro 14, French Top 14 and Super Rugby - Schoeman, R.; Schall, R. (International Journal of Performance Analysis in Sport, 2019)
This study examined the relationship between team performance indicators and five characteristics of team success (final log position, league points, points difference, points scored and points conceded) over a full season in four major rugby union competitions. Number of tries scored was the most significant (p < .0001) predictor of all five team success characteristics. Univariate analysis also identified stolen line-outs, tackles completed percentage, line breaks, tackle breaks, turnovers won, and total mauls as significant predictors of team success. Multiple regression analysis of performance indicators for team success suggested that team success is multifactorial, and selected performance indicators constitute independent aspects for winning the game. Different sets of performance indicators selected for points scored versus points conceded suggested performance indicators that are significantly associated with offensive and defensive capabilities, respectively. The most important indicators of defensive performance are line-outs stolen and percentage of tackles completed, while line breaks are the most important indicator of offensive performance. Improving offensive capability must be focused on achieving line and tackle breaks. Conversely, to improve defensive performance, the focus must be on stealing opposition line-outs and effective tackling.